(untitled) (Communications in Mathematical Research, 2019)
Wlpp semigroups are generalizations of lpp semigroups and regular semigroups. In this paper, we consider some kinds of wlpp semigroups, namely right-e wlpp semigroups. It is proved that such a semigroup S, if and only if S is the strong semilattice of L-right cancellative planks; also if and only if S is a spined product of a right-e wlpp semigroup and a left normal band.